Beyond Compliance: Washback Dynamics of Embedded Assessment Practices in Flipped Learning Environments Among EFL Undergraduates - Tinur Rahmawati Harahap; Yulia Rizki Ramadhani; Rosni Harahap; Tinur Rahmawati Harahap; Yulia Rizki Ramadhani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Flipped learning has transformed higher education through frequent embedded assessment; however, limited research has examined its washback effects on students’ learning behavior. This study investigated positive and negative washback perceptions among undergraduate students in a flipped English as a Foreign Language (EFL) program and introduced the concept of a high-density washback environment (HDWE). A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 60 undergraduate students at a public university in North Sumatra, Indonesia, using a validated 14-item Washback Perception Questionnaire and analyzed through descriptive statistics, paired-samples t-tests, and PLS-SEM confirmatory composite analysis. Qualitative data were obtained through semi-structured interviews and one focus group discussion involving six participants and analyzed using Reflexive Thematic Analysis. Positive washback was perceived at a high level and significantly exceeded moderate negative washback. Three qualitative themes emerged: self-regulated learning through pre-class assessment, cumulative assessment burden, and strategic compliance as ambivalent washback. The findings indicate that flipped learning assessment generally promotes positive learning behavior, although some responses reflect peer-mediated surface preparation rather than deep independent learning. The study proposes ambivalent washback as a distinct theoretical category and highlights assessment scheduling and instructional transparency as key factors influencing washback quality.